2007
DOI: 10.1021/bi7012799
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Domain Mobility and Enzymatic Reaction of l-Rhamnulose-1-phosphate Aldolase,

Abstract: The enzyme l-rhamnulose-1-phosphate aldolase from Escherichia coli participates in the degradation pathway of l-rhamnose, a ubiquitous deoxy-hexose. It is a homotetramer of the rare C4-symmetric type with N-terminal domains protruding like antennas from the main body. A mobility analysis of the enzyme gave rise to the hypothesis that an anisotropic thermal antenna motion may support the catalysis (Kroemer et al., Biochemistry 42, 10560, 2003). We checked this hypothesis by generating four single mutants and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The L-rhamnulose-1-P aldolase domain in RhaE is distantly homologous to class II aldolases including the analogs enzyme, RhaD, and the L-fuculose-1-P aldolase, FucA, from E. coli . The tertiary structures and catalytic mechanisms for these enzymes have been determined (Dreyer and Schulz, 1996; Grueninger and Schulz, 2008). We aligned the amino acid sequences of all three enzymes using the multiple protein sequence and structure alignment server PROMALS3D (Pei et al, 2008) (Figure S7 in Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
“…The L-rhamnulose-1-P aldolase domain in RhaE is distantly homologous to class II aldolases including the analogs enzyme, RhaD, and the L-fuculose-1-P aldolase, FucA, from E. coli . The tertiary structures and catalytic mechanisms for these enzymes have been determined (Dreyer and Schulz, 1996; Grueninger and Schulz, 2008). We aligned the amino acid sequences of all three enzymes using the multiple protein sequence and structure alignment server PROMALS3D (Pei et al, 2008) (Figure S7 in Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%
“…The N-domain contribution is much larger than all the components of the C-domain. These modes therefore represent rotational motions of the N-domain with respect to the Cdomain, as was captured by the crystallographic ATFs in references [22,23] . The relative contribution of the calculated modes may be different in the crystal, [14,15,44] even so, the agreement of the calculated modes and the ATF in the description of the N-domain rotation is very good.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The FucA model drawings can be found in Figure S4 in the Supporting Information. For the distance values, see [26] and RhuA, [22,23] respectively. These similar k cat values do not agree with RhuAs energy barrier being sevenfold smaller than FucAs.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…RhaD from E. coli (RhaD E.coli ) is a homotetramer of the rare C4-symmetric type, containing two molecules of Zn 2+ per enzyme complex, and each subunit is composed of 274 amino acid residues with a molecular weight of 30,149 Da [26,27]. Interestingly, Fessner et al first reported in 1991 that RhaD E.coli can also tolerate aldehyde with D-configuration, such as D-GA, as an acceptor, and we discovered in our previous study that Downloaded by [New York University] at 23:35 29 July 2015…”
mentioning
confidence: 99%